Contributions of Observed Parent Socialization of Coping and Skin Conductance Level Reactivity to Childhood Adjustment. Issue 1 (18th December 2016) - Stanger, Sarah; Abaied, Jamie; Wagner, Caitlin; Sanders, Wesley
Abstract : This research examined the longitudinal association between parent socialization of coping and child adjustment, as well as the moderating role of children's skin conductance level reactivity (SCLR). Participants were a community sample of children ( n = 64, M age = 9.02, 54.5% females, 93.2% Caucasian) and their parent(s). Parent coping suggestions were observed while their child engaged in a stressful challenge task, during which the child's SCLR, a measure of children's physiological reactivity to stress, was also measured. Parent(s) completed the Child Behavior Checklist (Achenbach & Rescorla, 2001) at baseline and a 6‐month follow‐up to assess internalizing and externalizing problems. Results revealed that secondary control engagement suggestions predicted fewer internalizing problems over time. In addition, disengagement suggestions predicted fewer externalizing problems over time among children with high SCLR. This study provides evidence that parent coping suggestions serve as a resource that protects youth from developing adjustment problems.